Spatial‐frequency features of radiation produced by a step‐wise tapered undulator. (26th March 2021) - Trebushinin, Andrei; Serkez, Svitozar; Veremchuk, Mykola; Rakshun, Yakov; Geloni, Gianluca
Abstract : Spatial frequency radiation properties from a step‐wise magnetic structure of an undulator are studied. This magnetic scheme is the most suitable for the superconducting undulators and provides the radiation properties that facilitate developing future beamlines dedicated to micro‐probing. Abstract : A scheme to generate wide‐bandwidth radiation using a step‐wise tapered undulator with a segmented structure is proposed. This magnetic field configuration allows to broaden the undulator harmonic spectrum by two orders of magnitude, providing 1 keV bandwidth with spectral flux density exceeding 10 16  photons s −1 mm −2 (0.1% bandwidth) −1 at 5 keV on the sample. Such a magnetic setup is applicable to superconducting devices where magnetic tapering cannot be arranged mechanically. The resulting radiation with broadband spectrum and flat‐top shape may be exploited at a multipurpose beamline for scanning over the spectrum at time scales of 10–100 ms. The radiation from a segmented undulator is described analytically and derivations with numerical simulations are verified. In addition, a start‐to‐end simulation of an optical beamline is performed and issues related to the longitudinally distributed radiation source and its image upon focusing on the sample are addressed.